The sundown speech - Estleman, Loren D. (Estleman, Loren D. Amos Walker novels., 2015)
"Amos Walker is hired by Helen and Dante Gunner, a bohemian Ann Arbor couple, to find Jerry Marcus, a film director who has disappeared with their investment money. It's one of Walker's easiest jobs to date. In just a few short hours, Walker locates Marcus in his bedroom...murdered, his body shoved into a cupboard, a bullet through his head. This case is opened and shut quickly, but Walker can't quite let it go. When Dante is arrested for the murder Walker finds himself again in Helen's employ, this time trying to prove that Dante didn't do it. When Walker interviews Holly Zacharias, a college student who was the last person to see Marcus alive, things get interesting. Because if Marcus is dead, and Dante is his killer, then who is driving by in the Crown Vic, shooting at Walker and Holly? Jerry Marcus just might still be alive, and his plans may be worse than anything Walker can imagine"--